Penerapan Sistem Monitoring Pergeseran Tanah berbasis Internet of Things (IoT) di Daerah Aliran Sungai (DAS) Kahayan, Kota Palangka Raya - Jefriyanto, Wilson; Samudra, Agung; Adelia, Kadek Ayu Cintya; Bryan, Kevin; Sukoco, Yoricho Costapierro (Jurnal Pengabdian Kampus, 2023)
Landslides occur as a result of a geological process caused by the displacement of rock or soil masses. In general, landslides are caused by shifting soil and excessive water content due to high rainfall. One of the processes that occur in rivers is sedimentation With the entry of sediment into the river flow, it will result in increased river surface flow and deposition which causes siltation of the river. This siltation will greatly affect the capacity of the river when the rainy season arrives, because it can cause floods. For this reason, assistance and training are needed to increase community knowledge about the use of Internet of Things (IoT) based monitoring system tools around the Kahayan river basin. IoT is a technology that allows smart objects, things, and machines to be connected via the internet so that data can be received in real time. The people of Pahandut Village were enthusiastic in participating in the socialization activities provided and felt the benefits of increasing knowledge starting from an understanding of the Internet of Things and the use of monitoring system tools for land shifts. Based on the evaluation results, it is known that participants have increased knowledge and insight into the Internet of things and its application in this case the soil shift monitoring system tool which will later be installed in residential areas around the watershed.